2020
DOI: 10.1038/s41467-020-16066-2
|View full text |Cite
|
Sign up to set email alerts
|

Context specificity of the EMT transcriptional response

Abstract: Epithelial-mesenchymal plasticity contributes to many biological processes, including tumor progression. Various epithelial-mesenchymal transition (EMT) responses have been reported and no common, EMT-defining gene expression program has been identified. Here, we have performed a comparative analysis of the EMT response, leveraging highly multiplexed singlecell RNA sequencing (scRNA-seq) to measure expression profiles of 103,999 cells from 960 samples, comprising 12 EMT time course experiments and independent … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
313
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 193 publications
(341 citation statements)
references
References 62 publications
26
313
2
Order By: Relevance
“…Of note, cellular plasticity conferred by EMT and other mechanisms that lead to morphological and functional changes requires robust reprogramming of gene expression programs. For example, several thousand genes change their expression in a context-dependent manner during EMT [ 41 ]. These profound changes require multiple layers of regulation, from transcription, to post-transcriptional RNA processing, to translational and post-translational modifications.…”
Section: Introductionmentioning
confidence: 99%
“…Of note, cellular plasticity conferred by EMT and other mechanisms that lead to morphological and functional changes requires robust reprogramming of gene expression programs. For example, several thousand genes change their expression in a context-dependent manner during EMT [ 41 ]. These profound changes require multiple layers of regulation, from transcription, to post-transcriptional RNA processing, to translational and post-translational modifications.…”
Section: Introductionmentioning
confidence: 99%
“…We analyzed the published datasets ( Cook and Vanderhyden, 2020 ) with ovarian OVCA420 cancer cell line capable of undergoing EMT. This cell line, which normally shows an epithelial morphology, was exposed to known EMT-inducing factors: TGFB1, EGF, and TNF, respectively, to promote EMT.…”
Section: Resultsmentioning
confidence: 99%
“…We started with trajectory reconstruction on the time-series datasets of an OVCA420 cancer cell line undergoing EMT induced by three different external signal (TGFB1, EGF, and TNF) and uncovered the existence of multiple ICSs displaying hybrid epithelial and mesenchymal features. Analysis of scRNA-seq previously demonstrated that EMT induction by TGFB1, EGF, and TNF is carried by context-specific signaling pathways ( Cook and Vanderhyden, 2020 ). Here, we show striking differences in the EMT population dynamics as well.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These scores, and scRNA-seq across a range of cancer cell lines, indicate a continuum in the gene expression landscape of EMP in both tumours and cell lines [Cursons et al, 2018, Karacosta et al, 2019a, Cook and Vanderhyden, 2020]. Given that EMP often involves changes in cellular morphology too, an EMP continuum in the morphological landscape is also being increasingly characterized recently [Leggett et al, 2016 The term metastable state was coined to describe the instability of these E/M hybrid cells [Klymkowsky andSavagner, 2009, Jia et al, 2018], although it may not apply equally to all E/M hybrids.…”
Section: Figure 1: Emp and The E/m Hybrid State Schematic Representamentioning
confidence: 99%